EFFECTIVENESS OF COPING STRATEGIES ON STRESS AND COPING AMONG THE CAREGIVERS OF ALCOHOL DEPENDENTS AT SELECTED DE-ADDICTION CENTRES, THANJAVUR - PROF. MRS.VANITHA INNOCENT RANI, M.SC (N); Dr.J.VENKATESAN; Dr,R.VIJAYARAGAVAN (International Journal of Pharma and Bio Sciences, 2016)
Alcohol is hard to avoid now a days. It has become a part of modern life. Alcohol can be very destructive for a lot of people, most especially the people who suffer and their family also suffers with the alcoholic dependents. Care givers of alcohol dependents must be empowered by teaching how to handle stress and cope up with the situation by the use of coping strategies. A quasi experimental study was done to assess the effectiveness of coping strategies on stress and coping among the care givers of alcohol dependents at selected de-addiction centers,Thanjavur. Non-equivalent control group pretest –post test design was carried out among 80 caregivers. The samples were selected by using Non probability purposive sampling technique and Rating Scales was used to collect the data. The statistical analysis revealed that, the calculated ‘t’ test value for stress (‘t’=22.96) and coping (‘t’=26.60) had a significant difference between the pre and post test levels of stress and coping among the caregivers of alcohol dependents at 0.05 level of significance. The correlation between the post test scores of stress and coping ‘r’ value (r= -0.7) for both groups. Hence the coping Strategies was significantly effective in improving the coping and reduction of stress among the caregivers of alcohol dependents.